Antecedents of Referring Healthcare-provider Engagement and its Impact on Willingness to Re-refer - Wijaya, Reisa Melisa; Antonio, Ferdi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Expansion of the healthcare sector in emerging nations aligns with the growth of private hospitals. This situation gives private hospitals some new challenges, like how to provide good quality care while growing the business, such as increasing the number of patients. An increasing number of patients is related to the referral system and healthcare providers. However, limited studies explained factors influencing healthcare provider engagement (HCPE) associated with willingness to re-refer within healthcare providers (WRH). This study investigated the relationship between factors influencing HCPE toward WRH within healthcare providers. A quantitative survey with a cross-sectional technique with a questionnaire asked 181 healthcare provider who usually refers patients to RSKK. Partial least squares structural equation modelling (PLS-SEM) was utilized to analyze the data. The result of study showed that five of the six antecedents from HCPE were significant (p-value0.05), and the HCPE showed a substantial relationship with WRH (p-value0.05). As conclusion, patient-specialist interaction has an essential relation with HCPE. Furthermore, HCPE has a crucial relationship with WRH. Therefore, the hospital management needs to prioritize this part more to encourage HCPE. This study shows antecedents from HCPE related with WRH and this model can be replicated in different hospitals as the contribution.